Sociocultural and economic determinants of adolescent fatherhood among Particularly Vulnerable Tribal Groups in Eastern India: a qualitative study from Jharkhand - Minj, Rohit Ranjan Paul; Toppo, Namita Francis; Oberoi, Anmol; Gupta, Saloni (International Journal Of Community Medicine And Public Health, 2026)
Background: Adolescent fatherhood among Particularly Vulnerable Tribal Groups (PVTGs) is an underexplored public health issue in India. Existing research has focused predominantly on adolescent mothers, leaving pathways to early fatherhood among tribal boys largely unexamined. This study explores the socio-cultural and economic determinants of adolescent fatherhood among PVTGs in Jharkhand. Methods: A qualitative study was conducted from December 2025 to February 2026 in Patamda block, East Singhbhum, Jharkhand. Thirty-four males (aged 14-34 years) from Sabar, Birhor, and Pahariya PVTG communities were enrolled using purposive and snowball sampling. Semi-structured interviews, focus group discussions, and field observations were conducted; thematic analysis continued until saturation. Results: Early marriage was identified as the primary and socially normalised pathway to adolescent fatherhood, with 51.6% of participants having married before the age of 18 years (mean age at marriage: 18.0±3.5 years). All 34 participants (100%) reported no awareness of family planning methods prior to becoming fathers. Tobacco use was reported in 91.2% and alcohol use in 82.4% of households. Educational discontinuation was near-universal (97.1%), with financial constraints and early entry into wage labour as predominant reasons. A substantial proportion reported peer (64.7%) and sibling (61.8%) exposure to adolescent parenthood. All participants (100%) expressed a desire that the next generation should not become adolescent parents. Conclusions: Adolescent fatherhood in this context is shaped by structural poverty, early marriage norms, educational discontinuation, and absence of reproductive health services. Gender-inclusive, community-embedded interventions engaging adolescent boys, and improvements in education, livelihood, and health systems are urgently needed.